Faktor – Faktor Penciri Status Ketenagakerjaan Penduduk Usia Kerja Terdidik Di Sulawesi Utara - Erickson, Carlos; Laoh, Olly Esry; Rotinsulu, Wiske (JURNAL ILMIAH SOCIETY, 2015)
This study aims to peel identifier factors of employment status on the educated working age population in North Sulawesi. Moreover, in this paper also calculated the deficit of decent work opportunities in North Sulawesi in 2015. Sources of key data used in the analysis and calculations using secondary data Sakernas 2013. Methods of analysis using multinomial logistic regression. Processing results obtained three significant variables: age, number of household members who work, and gender. Logistic regression models were obtained form 68.6% concordance rate. For a decent amount of work that needs to be createdat least 107 thousands between 2012 and 2015 or 35 thousands per year, if the target of 6.62% poverty rate and unemployment rate of 3.94% in 2015 to be achieved. The study recommends further research by incorporating several new variables among household income. Government needs to empower the productive population and women. Other decent employment targets also need to be developed such as a decrease in youth unemployment. Â Keywords: Labor, Population of Working Age